2022
DOI: 10.1039/d2sm00458e
|View full text |Cite
|
Sign up to set email alerts
|

Polymer brush-based nanostructures: from surface self-assembly to surface co-assembly

Abstract: Surface structure plays an important role in the practical applications of materials. The synthesis of polymer brushes on solid surface has emerged as an effective tool for tuning surface properties....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 221 publications
(279 reference statements)
0
6
0
Order By: Relevance
“…Patchy particles can be constructed from patterned coatings, functionalized molecules, DNA, and other enthalpic means. [9][10][11][12] Spontaneous pattern formation on the surface of a sphere 13 offers an interesting route to fabrication of patchy colloids, 3 for example, by confining nanoparticles in spherical droplets one obtains unexpected configurations. [14][15][16] For a small number of particles, minimum energy configurations result in the formation of clusters with symmetries that are inconsistent with long-range order that may result in a variety of phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Patchy particles can be constructed from patterned coatings, functionalized molecules, DNA, and other enthalpic means. [9][10][11][12] Spontaneous pattern formation on the surface of a sphere 13 offers an interesting route to fabrication of patchy colloids, 3 for example, by confining nanoparticles in spherical droplets one obtains unexpected configurations. [14][15][16] For a small number of particles, minimum energy configurations result in the formation of clusters with symmetries that are inconsistent with long-range order that may result in a variety of phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Surface nanostructures can be fabricated by directly immobilization of the nanoparticles on the substrates . Recently, it was reported that covalently bonded polymer brushes were able to make surface coassembly with BCP chains in selective solvents and a range of surface nanostructures could be fabricated. , To demonstrate the surface coassembly of polymer brushes on TA coatings and free BCP chains, qPDMAEMA 36 - b -PS 135 chains were anchored onto the TA coatings through the electrostatic interaction and hydrogen bonding (Scheme ), and the coassembly of the noncovalently anchored PS brushes and BCP chains in a selective solvent was investigated. Herein, THF was used as a solvent for all the components, and methanol was used as a selective solvent for PDMAEMA and a precipitant for PS.…”
Section: Resultsmentioning
confidence: 99%
“…Surface coassemblies of covalently bonded polymer brushes and block copolymer (BCP) chains in selective solvents provide an effective method to tune the surface morphologies and surface chemical compositions. Herein, the synthesis of polymer brushes and removable surface nanostructures anchored on TA coatings are studied. As shown in Scheme , TA molecules were coated on the surfaces of amino-modified silica nanoparticles (SiO 2 -NH 2 ) through hydrogen bonding and electrostatic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] This ability to introduce and control surface modifications on nanoparticles has opened up several new avenues for achieving self-assembly of a wide variety of composite structures. [16][17][18][19][20][21][22][23][24] The study of the effect of these modifications on the mechanical properties of the resulting nanocomposite is of fundamental interest for the design of novel hybrid materials. 25 Of the different surface modifications, the variation of graft density and inclusion of free-end functional groups is of particular interest as they play an important role in modifying the interactions between PGNs.…”
Section: Introductionmentioning
confidence: 99%
“…8–15 This ability to introduce and control surface modifications on nanoparticles has opened up several new avenues for achieving self-assembly of a wide variety of composite structures. 16–24 The study of the effect of these modifications on the mechanical properties of the resulting nanocomposite is of fundamental interest for the design of novel hybrid materials. 25…”
Section: Introductionmentioning
confidence: 99%